A Modified 4×4 Butler Matrix Based Switched Beamforming Network with Five Beams - Al-Marwan, Qutaibah Khaled (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
In this work 4x4 Butler matrix with 1×4 microstrip patch antenna array has been proposed to form a switched beamforming network operating at 3 GHz. This beamformer generates 4 orthogonal beams. 4x4 Butler matrix comprises 4 directional couplers, two phase shifters and two crossovers. The directional couplers have been used to divide the power equally with 90 ̊ phase shift, the phase shifters performs the phase delay in the design and the crossover works for isolation. All simulation results of these components matched the theory. Linear 1×4 microstrip patch antenna array elements have been matched using inset feed technique. These elements had a good performance at the design frequency. The CST MICROWAVE STUDIO SUIT was used for simulations. The total size of the Butler matrix is 104 mm×100mm. The return loss obtained was less than –15 dB and the output power distribution was in the range of -6 to -8 dB at the 3GHz design frequency. The four beams have been obtained in the directions -14°, -42°, 42° and 14° with a narrow beamwidth and with a gain of 11.4 dB, 11.2 dB, 11.2dB, and 11.4dB respectively A modified Butler matrix also has been proposed to generate a fifth beam at together with the original four beams obtained in the conventional design. The modification increased the scan capability Keywords: 4x4 Butler matrix, beamforming, linear array, radiation pattern.

ÖZ: Bu çalışmada, 3 GHz frekansında 1x4 mikro şerit yama anten dizili, anahtarlamalı hüzme oluşturma ağı olan bir 4x4 Butler matrisi önerilmiştir. Bu hüzme oluşturucu, 4 dik hüzme üretmektedir. 4x4 Butler matrisi 4 yönlü birleştirici, iki faz kaydırıcı ve iki geçitten oluşmaktadır. Yönlü birleştiriciler, gücü 90 ̊ faz kayması ile eşit olarak bölmek, faz kaydırıcılar tasarımda faz gecikmesi gerçekleştirmek ve geçitler de izolasyon sağlamak için kullanılmıştır. Bu tasarımdan elde edilen sonuçlar teori ile uyum içerisindedir. 1×4 Mikro şerit yama anten dizi elemanları, içe besleme tekniği kullanılarak uyumlaştırılmıştır. Bu elemanlar tasarım frekansında iyi performans göstermiştir. Çalışma Mikrodalga CST benzetim yazılımı kullanılarak gerçekleştirilmiştir. Butler matrisinin boyutları 104 mm × 100 mm'dir. 3GHz tasarım frekansında elde edilen dönüş kaybı -15 dB'den az, çıkış gücü dağılımı ise -6 ila -8 dB aralığındadır. -14 °, -42 °, 42 ° ve 14 ° yönlerinde, sırasıyla 11.4 dB, 11.2 dB, 11.2dB ve 11.4dB kazancı olan dar hüzme genişliğine sahip dört hüzme elde edilmiştir. Geleneksel Butler matris tasarımında değişiklik yapılarak, elde edilen dört hüzmeye ek olarak 0° yönünde beşinci bir hüzme elde edilmiş ve tarama kapasitesi artırılmıştır. Anahtar Kelimeler: Butler matrisi, hüzme oluşturma, doğrusal dizi, radayassyon deseni
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2017. Supervisor: Assist. Prof. Dr. Rasime Uyguroğlu.
Keywords: Electrical and Electronic Engineering; Antennas (Electronics); Wireless Communication Systems-Adaptive Antennas-Smart Antennes; 4x4 Butler matrix; beamforming; linear array; radiation pattern